Gustav Ungerer, A Spaniard in Elizabethan England- The correspondence of Antonio Pérez's exile. Tamesis Books, London, 1974, 1976; 2 ts.: xxxix + 505, 450 pp. (Monografías, 27, 54). - Soons, Alan (El Colegio de México, 1979)
Se reseñó el libro: A Spaniard in Elizabethan England- The correspondence of Antonio Pérez's exile.